Multilingualism in Contemporary Sephardic Children’s Literature - Agnieszka August-Zarębska (Barnboken: Tidskrift för Barnlitteraturforskning)
This article explores the resurgence of contemporary Sephardic children’s literature, with a particular focus on its multilingual nature as a central feature. The study aims to demonstrate how the use of multiple languages within a book serves as a tool to keep young Sephardic readers connected to Ladino – their heritage language – which, nowadays, is considered severely endangered. The methodological approach is based on Jeffrey Shandler’s concept of post-vernacularity, positioning contemporary Judeo-Spanish children’s literature as a post-vernacular phenomenon. The selected books were published in Israel and the United States between 2010 and 2023. This research categorises these works based on the various configurations of multilingualism, which may manifest as direct translations or the use of different languages (and alphabets) in distinct sections of the text and in the pictures. The study concludes that multilingual children’s literature offers a meaningful way for young Sephardim to connect with their cultural roots and engage with Ladino culture.